Synthesis and characterization of curcuminoids by claisen-schmidt condensation and their cytotoxic effects on hela and K562 cancer cell lines - Siti Noor, Hajar Zamrus (2018)
Cancer is one of leading causes of death worldwide with the number of cases is expected to rise by 70% over the next two decades. These facts have lead researchers to continue studying how to treat cancer by find a new potential drug to replace the standard anti-cancer drugs such as doxorubicin which has side effects. Numerous natural compounds have been extensively investigated for their potential use in cancer prevention over decades. Curcumin from Curcuma longa has caught attention among researchers, is a highly promising natural compound that can potentially be used for chemoprevention of various cancers. Curcumin fulfils the characteristics for an ideal chemopreventive agent with its low toxicity, affordability and easy accessibility. But due to structurally instable, low solubility and poor bioavailability, the mono-ketone of curcuminoids were synthesized to improve its structure and poor bioavailability. About 20 curcuminoids were synthesized by using different substituted aldehydes and different ketones under Claisen-Schmidt condensation reaction method. The products were purified by using column chromatography, thin layer chromatography and crystallization processes. The chemical structures of the synthesized compounds were elucidated by using UV-VIS spectroscopy, Fourier transform infrared spectrometer (FTIR), Mass spectroscopy (MS) and Nuclear magnetic resonance spectrometer (NMR) spectroscopy. The compounds were screened for their cytotoxicity effects on HeLa human cervical carcinoma and K562 cancer cell lines by using MTT assay. Among these derivatives, 21 (IC50 = 12.50 ± 1.30), 22 (IC50 = 11.00 ± 2.80), 23 (IC50 = 9.00 ± 1.20), 26 (IC50 = 12.00 ± 1.60), 28 (IC50 = 11.00 ± 2.10), 29 (IC50 = 15.00 ± 1.60), 30 (IC50 = 15.00 ± 1.20), 31 (IC50 = 14.00 ± 1.40), 32 (IC50 = 11.00 ± 1.30), 33 (IC50 = 11.00 ± 1.20) and 34 (IC50 = 6.00 ± 1.20) showed high cytotoxic effects on HeLa human cervical carcinoma cell lines. Meanwhile, compounds 22 (IC50 = 6.50 ± 0.80), 23 (IC50 = 16.00 ± 1.30), 32 (IC50 = 15.00 ± 1.90) and 33 (IC50 = 12.50 ± 0.95) showed high cytotoxic effects against K562 cancer cell lines. Therefore, some compounds were found to show higher cytotoxicity effect against HeLa and K562 cancer cell lines in comparison to doxorubicin used as standard.